Active Steering Actuator Fault Detection for an Automatically-Steered Electric Ground Vehicle - Zhang, Hui; Wang, Junmin (IEEE transactions on vehicular technology, 2017)
In this paper, we investigate the actuator fault detector design problem for an electric ground vehicle (EGV) that is equipped with an active front-wheel steering system. Since the EGV can be steered by a motor automatically, it is desired to design a fault detector for the steering actuator for safety reasons. A two degree of freedom lateral nonlinear vehicle model is established. The nonlinear vehicle model is converted to a linear-parametervarying (LPV) form and the scheduling vector is related to the vehicle longitudinal velocity. Since it is not easy to measure the longitudinal velocity precisely, the uncertain measurement on the longitudinal velocity is considered and the weighting factors of LPV submodels are subject to uncertainties. Based on the uncertain LPV model, a gain-scheduling fault detector is proposed and an augmented system is obtained. The desired steering angle and the faulty steering angle are both involved in the augmented system. As the steering angle generally has a low-frequency working range, the steering angle amplitude spectrums of three different maneuvers are studied, and the frequency working range is determined. The stability, the H-performance, and the H ∞ , performance of the augmented system are all exploited. Based on the analysis results, the mixed H_/H ∞ , fault detector design method is developed. An experimental test is used to show the performance of the designed fault detector.